2020
DOI: 10.1007/s11419-020-00544-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile of the synthetic drug 4,4′-dimethylaminorex in urine by LC–MS-based techniques: selection of the most suitable markers of its intake

Abstract: Purpose In this study, the phase I and II metabolic pathways of 4,4′-dimethylaminorex were characterized to select the marker(s) of intake allowing the unequivocal identification of this novel psychoactive substance in urine samples. Methods The metabolic profile of 4,4′-dimethylaminorex was characterized using both in vitro and in vivo models. In detail, for the in vitro experiments, either pooled human liver microsomes or recombinant cytochrome P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…At present, no in vivo pharmacological studies have been performed with the (±)trans-4,4 -DMAR stereoisomer whilst only one in vitro pharmacodynamic study has been published showing that (±)trans-4,4 -DMAR is a substrate-type releaser at the DAT, NET transporters and a SERT uptake blocker in rat brain tissue with a lower potency than the (±)cis-4,4 -DMAR stereoisomer [14]. However, in a recent pharmacokinetic study it was found that whilst the (±)cis-4,4 -DMAR compound is metabolised and excreted in the mouse urine, the (±)trans-4,4 -DMAR stereoisomer is not metabolised [84] suggesting a stereoselective metabolism and disposition of 4,4 -DMAR. This is common in stereoisomers of a drug that generally metabolised with different metabolic profile [85] both in pharmaceutical [86] and in abusing drugs [87,88].…”
Section: Convulsions and Lethalitymentioning
confidence: 99%
See 1 more Smart Citation
“…At present, no in vivo pharmacological studies have been performed with the (±)trans-4,4 -DMAR stereoisomer whilst only one in vitro pharmacodynamic study has been published showing that (±)trans-4,4 -DMAR is a substrate-type releaser at the DAT, NET transporters and a SERT uptake blocker in rat brain tissue with a lower potency than the (±)cis-4,4 -DMAR stereoisomer [14]. However, in a recent pharmacokinetic study it was found that whilst the (±)cis-4,4 -DMAR compound is metabolised and excreted in the mouse urine, the (±)trans-4,4 -DMAR stereoisomer is not metabolised [84] suggesting a stereoselective metabolism and disposition of 4,4 -DMAR. This is common in stereoisomers of a drug that generally metabolised with different metabolic profile [85] both in pharmaceutical [86] and in abusing drugs [87,88].…”
Section: Convulsions and Lethalitymentioning
confidence: 99%
“…Urine samples were treated and analysed through a protocol already used by our group for the analysis of the excretion of stimulant drugs in mice [84,112]. Briefly, our protocol allowed the conversion of conjugated metabolites (i.e., sulfo-and glucorono-conjugates) to phase I metabolites after two hydrolysis steps.…”
Section: Excretion Studiesmentioning
confidence: 99%
“…This study aimed to define the phase I biotransformation pathways of mexedrone. For this purpose, due to the strict regulations for conducting controlled administration studies in humans and animals, we have followed the same experimental strategy already followed in similar studies, [36][37][38][39][40] focusing our attention on the in vitro metabolic profile of mexedrone, studied using human liver microsomes and isolated CYP450 recombinant isoforms.…”
mentioning
confidence: 99%
“…An Agilent 1290 Infinity II UHPLC with a binary gradient system and an automatic injector (Agilent Technologies, Cernusco sul Naviglio, Milano, Italy) was used for the chromatographic separation. The instrument was equipped with an Agilent ZORBAX Eclipse Plus C18 column (100 × 2.1 mm i.d., particle size 1.8 μm) ( 37 ). The detector was an Orbitrap Q Exactive (Thermo Fisher Scientific) with an ESI source.…”
Section: Methodsmentioning
confidence: 99%